Beyond sovereignty : issues for a global agenda - Cusimano, Maryann K. (Boston : Bedford/St. Martins, 2000)
[This book] begins with an outline of the rise of transsovereign problems, open markets, open societies, and open economies, a historical description of sovereignty, as well as a review of current theories concerning whether sovereignty is receding, changing, or remaining as powerful as ever. The chapters that follow ... consider various transsovereign issues; their connections with open economies, societies, and technologies; and potential policy situations. These issue chapters are followed by ones that describe the changing roles of nonstate actors, such as intergovernmental and nongovernmental organizations and multinational corporations.... The volume concludes by returning to theoretical arguments about the future of sovereignty.... [This book] is written [for] students in introductory courses in international relations, U.S. foreign policy, global issues, or globalization ... -Pref.
Includes bibliographical references.
Keywords: Globalization; International cooperation; Sovereignty